Advanced optics using aspherical elements - Tiziani, Hans J.; Hentschel, Rüdiger, 1949-; Braunecker, Bernhard (SPIE, 2008)
Modern optical systems rely on leading-edge production technologies, especially when using aspherical optical elements. Due to the inherent complexity of aspheres, all efforts to push the technological limits are risky. Thus, to minimize risk, clear decisions based on a good understanding of technology are indispensable. This compendium is written as an optical technology reference book for development and production engineers. With contributions from worldwide experts, this book aids in mitigating the risk in adopting new asphere production technologies.
"SPIE digital library."
Includes index.
Keywords: Optical instruments -- Design and construction.; Aspherical lenses.; elektronické knihy; electronic books